Domosławski – bohater czy bluźnierca? Krytykowanie w polsko-niemieckim dyskursie na podstawie tytułów artykułów prasowych - Hanus, Anna (Stylistyka, 2019)
The power of language seems to come to the fore, especially in the media world in all its gradations. This paper discuses Polish-German headlines in press discourse concerning the scandalous biography Kapuœciñski non-fiction, with the aim to investigate the degree of explicitness in expressing criticism with the use of negative judgemental illocutions. The basis for the text-linguistic analysis is the illocution structural analysis method developed further by H. Lenk and adapted to analysing press headlines. The article examines the usefullness of this method, pointing out its advantages and shortcomings, as well as other aspects, which can be meaningful while analysing the headlines.